1994
DOI: 10.1111/j.1476-5381.1994.tb14870.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of endothelial function with age in the mesenteric arterial bed of the normotensive rat

Abstract: 1Age-related changes in endothelial vasodilator function were studied in an in vitro preparation of the mesenteric arterial bed removed from male, normotensive, Wistar rats. 2 Animals were killed at 2, 12 or 22 months of age, the superior mesenteric artery was cannulated and the gut removed. The mesenteric arterial bed was perfused at a constant flow rate of 4 ml min-' and perfusion pressure was taken as an index of arteriolar tone. 3 The muscarinic agonist, carbachol, antagonized noradrenaline-induced vasocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 26 publications
3
18
1
Order By: Relevance
“…The adult rats used in the present paper are at the upper age limit for absence of change in vasomotion (Atkinson et al, 1994a(Atkinson et al, , 1994bCapdevilleAtkinson et al, 1995;Vandeputte et al, 1999;Tabernero et al, 2000). In fresh rings in the present experiment, NE-induced contraction was similar at both ages although iNOS mRNA expression was higher in rings from adult donors and the latter appeared to have a lower anti-oxidant capacity.…”
Section: Discussioncontrasting
confidence: 48%
“…The adult rats used in the present paper are at the upper age limit for absence of change in vasomotion (Atkinson et al, 1994a(Atkinson et al, , 1994bCapdevilleAtkinson et al, 1995;Vandeputte et al, 1999;Tabernero et al, 2000). In fresh rings in the present experiment, NE-induced contraction was similar at both ages although iNOS mRNA expression was higher in rings from adult donors and the latter appeared to have a lower anti-oxidant capacity.…”
Section: Discussioncontrasting
confidence: 48%
“…In the present study, however, we studied small mesenteric resistance arteries and renal arteries which already showed near 100% relaxation to ACh, i.e., unlike the aorta, there may not be much to be gained by ACE inhibition. Atkinson et al (1994) found improved maximal relaxation to ACh in mesenteric arteries of normal WAG/Rij rats after ACE inhibitor treatment. However, the untreated rats in their study developed a time-dependent decrease in maximal ACh induced dilation in mesenteric artery, suggesting an improvement of ACh induced relaxation due to prevention of age-induced endothelial dysfunction (Atkinson et al, 1994;Atkinson, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Atkinson et al (1994) found improved maximal relaxation to ACh in mesenteric arteries of normal WAG/Rij rats after ACE inhibitor treatment. However, the untreated rats in their study developed a time-dependent decrease in maximal ACh induced dilation in mesenteric artery, suggesting an improvement of ACh induced relaxation due to prevention of age-induced endothelial dysfunction (Atkinson et al, 1994;Atkinson, 1995). In our 3-week treatment compared with the treatment of several months of Atkinson et al (1994), reduction of age-induced dysfunction due to ACE inhibition could not be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the aging vascular endothelium experiences a progressive loss of release of eNO, associated with endothelial dysfunction . Reduced release of NO in response to endothelium‐dependent agonists has been demonstrated in aged arteries, including the brachial artery and coronary artery in humans and the aorta, carotid artery, and mesenteric artery in rats. The mechanism responsible for this age‐related endothelial dysfunction has not yet been clearly elucidated, but it might involve (1) changes in expression/and or coupling of eNOS, (2) increased breakdown of eNO due to an augmented production of reactive oxygen species (ROS), or (3) a gradual loss of antioxidant capacity that normally provides cellular protection against ROS .…”
Section: Metabolic Microvascular Dysfunction As a Driver Of Organ Agingmentioning
confidence: 99%